Analisis Pengaruh E-Commerce Terhadap Keputusan Pembelian Busana Muslim: Studi Kasus Mahasiswa Kota Palembang - Mulyani Rizki; Defatrian Defatrian (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Various factors make Muslim fashion continue to develop. The continued increase in demand for Muslim fashion, the growth of hijab communities such as Hijabers Community, Hijabers Mom, and others, as well as the holding of various bazaars, Muslim fashion shows, hijab class activities on campuses, companies, recitations, or social gatherings really support the growth of this business in Indonesia. Water. Purchasing decisions are an important thing to pay attention to because this will certainly be a consideration of what marketing strategy the company will carry out next. The company's success in influencing consumers in purchasing decisions is strongly supported by efforts to build communication with consumers by building brands for consumers with marketing strategies, as well as innovating new variants of a product. E-Commerce is a new concept which is usually described as the process of buying and selling goods or services on the Internet or the process of buying and selling or exchanging products, services and information via information networks including the internet. e-commerce sells products to consumers online. Simply put, E-commerce is creating, managing and expanding commercial relationships online Judging from the phenomenon above, researchers are interested in researching the influence of E-commerce on Muslim clothing purchasing decisions among female students in the city of Palembang. The number of samples in this research was 100 respondents, this research used a quantitative approach. The data collection technique in this research uses a questionnaire, and the sampling technique uses a non-probability-purposive sampling method. The results of this study show that e-commerce has no influence on the purchasing decisions of Muslim clothing for Palembang city students.